Hubungan Kepatuhan Mengkonsumsi Makanan Tambahan dengan Peningkatan Berat Badan Ibu Hamil KEK (Kurang Energi Kronis) di Puskesmas Ratte - Harmawati Rustan; Kartini S; Hartati S (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The impact of Chronic Energy Deficiency (CED) on pregnant women includes a higher risk of delivering low birth weight (LBW) infants. This research employs a quantitative approach using a cross-sectional study design. The population and sample size consist of 42 individuals. Questionnaires are used for data collection. Data analysis employs the chi-square test. The results of the data analysis indicate a significant relationship between compliance in consuming supplementary food and weight gain among pregnant women with CED at Ratte Health Center, Tana Toraja Regency, with a p-value of 0.002, which is smaller than the α value of 0.05. It is recommended that health centers establish regular education programs focused on the nutritional needs of pregnant women with CED. Through these educational sessions, pregnant women can receive accurate and relevant information about the importance of supplementary food and its impact on health.